The Ultra Vires Doctrine In Administrative Law: A Malaysian Perspective - Gan, Ching Chuan (Journal of Malaysian and Comparative Law, 2019)
The doctrine of ultra vires is the central doctrine of Administrative Law. This doctrine envisages that the powers of the administrative or statutory agencies or bodies are conferred and limited by law and, therefore, any exercise of power (be it discretionary or rule-making or even adjudicatory) beyond the confines or limits imposed by law will render the action taken or decision so made ultra vires and therefore null and void.